Religion in civil society: the influence of black religious ecology on crime in the South - Thomson, Bob (Journal of quantitative criminology, 2021)
The civil society perspective predicts that civic and voluntary organizations promote the welfare of communities by enhancing social capital and cohesion. Here, I examine whether black Protestant churches, because of their dual emphasis on personal piety and social justice, function as agents of civil society in the southern United States by reducing crime, and whether structural context moderates the relationship between black religious ecology and crime.